Assessment of chitosan biopolymer encapsulated α-Terpineol against fungal, aflatoxin B1 (AFB1) and free radicals mediated deterioration of stored maize and possible mode of action. (1st May 2020) - Kumar Chaudhari, Anand; Singh, Akanksha; Kumar Singh, Vipin; Kumar Dwivedy, Abhishek; Das, Somenath; Grace Ramsdam, Mayondi; Dkhar, Mumtaz S; Kayang, Highland; Kishore Dubey, Nawal
Highlights: α-Terpineol was encapsulated into chitosan biopolymer via ionic-gelation. α-Terpineol loaded chitosan nanoemulsion (α-TCsNe) showed enhanced efficacy. α-TCsNe can potentially protect the maize sample from aflatoxin during storage. α-TCsNe did not alter the organoleptic attributes of maize during storage. α-TCsNe can be utilized as a novel antifungal preservative. Abstract: This study reports enhanced efficacy of encapsulated α-Terpineol to control fungal, aflatoxin B1 (AFB1 ) and free radicals mediated deterioration of stored maize samples. The α-Terpineol loaded chitosan nanoemulsion (α-TCsNe) was characterized through SEM, FTIR and XRD techniques. The α-TCsNe exhibited enhanced antifungal activity against aflatoxin secreting strain of Aspergillus flavus (AF-LHP-S1) and 12 other food borne moulds as well as AFB1 production at 0.4 and 0.3 µL/mL, respectively. Further, α-TCsNe inhibited ergosterol synthesis, methylglyoxal (the aflatoxin enhancer) content and enhanced cellular contents release. α-TCsNe showed enhanced radical scavenging activity with IC50 value equivalent to 39.57 and 6.23 µL/mL for DPPH and ABTS, respectively. In addition, α-TCsNe completely inhibited AFB1 production in stored maize samples during in situ investigation. Overall, α-TCsNe holds a promising potential and can be recommended as a novel antifungal preservative to improve the shelf-life of stored maize samples against fungal and aflatoxin contamination.